A follow-up study of post-COVID-19 syndrome in hospitalized children with Omicron variant infection in Wuhan - Tang, Chunjiao; Wang, Shouyi; Fan, Jingyi (Frontiers in Pediatrics, 2024)
Background Since the Chinese government changed its COVID-19 prevention and control policies, the rapid spread of the omicron variant resulted in a pervasive surge of infections throughout the nation, particularly affecting children. Although the acute symptoms of children infected with COVID-19 are milder compared to adults, the impact of post-COVID-19 syndromes (PCS) on the growth and development of children should not be ignored. The clinical manifestations, treatment methods, and long-term effects of children are significantly different from those of adults, making it necessary to understand the phenotype of children with PCS in order to effectively manage their health. Methods The study focuses on hospitalized children infected with omicron variant in Zhongnan Hospital of Wuhan University from December 7, 2022, to January 5, 2023. Three telephone follow-ups with the guardians was conducted at 4–5 weeks, 12–13 weeks, and 24–25 weeks after the patients' discharge to understand their prevalence, clinical characteristics, and risk factors of PCS. Results The age range of the 112 hospitalized pediatric patients was 0–13 years, with a median age of 19 months. After three follow-ups, 49.1% patients had PCS, while the incidence of PCS persisting 3 month was 21.4%, with a prevalence of PCS persisting 6 month of 10.7%. From the first follow-up phase to the third phase, there was a significant decrease in the incidence of PCS. In infants, the most common persistent symptom was sleep disorder (19.2%), followed by respiratory symptoms, diarrhea (8.2%), and decreased appetite (6.8%). In children and adolescents, decreased appetite was the most common persistent symptom (30.8%), followed by respiratory symptoms, fatigue (15.4%), and mood changes (15.4%). Decreased appetite was more common in the children and adolescents, while diarrhea and sleep disorders were more common in the infants. Binary logistic regression analysis and ordered logistic regression analysis showed that times of illness (OR = 1.671, 95% CI: 1.339–2.086) were positively correlated with the duration of symptoms. Times of illness was positively correlated with cough/expectoration (OR = 1.491, 95% CI: 1.039–2.138). Age (OR = 0.844, 95% CI: 0.755–0.944) and re-hospitalization (OR = 0.146, 95% CI: 0.022–0.969) were positively correlated with sleep disorders. Conclusions Children with Omicron variant may still experience PCS, but the incidence is lower compared to adults and compared to other variants and the incidence of PCS will gradually decrease over time. The symptoms of PCS differ between older children and infants and it is necessary to prevent recurrent illness for at least half a year after COVID-19 recovery. In order to further understand and ameliorate the impact of PCS on the health of children infected with COVID-19, subsequent follow-up studies will expand the scope, combine with objective follow-up contents, and establish an assessment and management system especially for children of different ages.